Comparison of Ultrasonic Wave Pretreatment and Microwave-KOH Combination Pretreatment in Producing Bioethanol Using Rice Husk Waste - Ardhiansyah, Hanif; Putri, Radenrara Dewi Artanti; Kusumaningrum, Maharani; Akbar, Faizal Reza Amirruddin; Fidiano, Daffa Bimo (Universitas Negeri Semarang, 2023)
Rice husk is a type of lignocellulosic biomass that can be chosen as a raw material for bioethanol production because it is abundant, cheap, and renewable. However, when it comes to lignocellulosic biomass, the main obstacle in using rice husks is the pretreatment process to remove the lignin content and prepare the lignocellulose so that it can be easily hydrolyzed. In this study, two combinations of pretreatment were used, namely microwave pretreatment and ultrasonic pretreatment, which used several variables. Microwave pretreatment uses variable time (2.5 minutes, 5 minutes, and 7.5 minutes) and power (100, 180 and 300 watts) as well as ultrasonic pretreatment uses variable time (20 minutes, 25 minutes, and 30 minutes) and power (70, 80 and 90 watts). The pretreatment results were hydrolyzed with sulfuric acid and fermented using saccharomyces cerevisiae yeast at varying times (3, 6, 9, 12, and 15 days). This research shows that microwave pretreatment is the most effective in reducing lignin. The lowest lignin content was 10.58% after 5 minutes and 180 watts of power. Bioethanol levels increased until the 15th day of fermentation, with the highest yield of 16%.